2023
DOI: 10.57187/smw.2023.40065
|View full text |Cite
|
Sign up to set email alerts
|

Use of epinephrine in anaphylaxis: a retrospective cohort study at a Swiss university emergency department

Abstract: AIMS OF THE STUDY: Anaphylaxis is a medical emergency and requires prompt treatment to prevent life-threatening conditions. Epinephrine, considered as the first-line drug, is often not administered. We aimed first to analyse the use of epinephrine in patients with anaphylaxis in the emergency department of a university hospital and secondly to identify factors that influence the use of epinephrine. METHODS: We performed a retrospective analysis of all patients admitted with moderate or severe anaphylaxis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 41 publications
(63 reference statements)
0
3
0
Order By: Relevance
“…One explanation for this could be an increased awareness of allergic reactions, since one third of the patients stated that they already had anaphylactic reactions in the past. On the other hand, emergency medical services and perhaps patients have a clearer therapeutic strategy, especially with the use of epinephrine [23]. However, epidemiologic data on anaphylaxis should be interpreted with caution: First, because anaphylactic events often occur outside hospitals, so the true rate of anaphylaxis may be underestimated after all [8].…”
Section: Suspected Triggersmentioning
confidence: 99%
See 2 more Smart Citations
“…One explanation for this could be an increased awareness of allergic reactions, since one third of the patients stated that they already had anaphylactic reactions in the past. On the other hand, emergency medical services and perhaps patients have a clearer therapeutic strategy, especially with the use of epinephrine [23]. However, epidemiologic data on anaphylaxis should be interpreted with caution: First, because anaphylactic events often occur outside hospitals, so the true rate of anaphylaxis may be underestimated after all [8].…”
Section: Suspected Triggersmentioning
confidence: 99%
“…According to international guidelines, gastrointestinal symptoms are eligible for therapy with intramuscular epinephrine for anaphylaxis [34]. In a previous study, we showed that especially patients with skin and gastrointestinal symptoms (anaphylaxis grade II) often do not receive the necessary therapy with epinephrine [23]. Therefore, when anaphylaxis is suspected, gastrointestinal symptoms must be actively sought.…”
Section: Suspected Triggersmentioning
confidence: 99%
See 1 more Smart Citation